Analisis Pengaruh Nilai Pelanggan dan CRM Terhadap Kepuasan dan Loyalitas Pelanggan di Toko Trio Taylor Manado - Sangian, Livie Meyland (Universitas Sam Ratulangi, 2015)
This research aims to discover the effects of customer value, customer relationship management on customer satisfaction and customer loyalty. The sample of this research is customers of Trio Taylor Store as many as 110 respondents. The Structural Equation Modeling (SEM) was used to analyze the data using the AMOS software. Research findings show that customer value has a positive significant effect on customer satisfaction and customer loyalty, while customer relationship management has significant effect on customer satisfaction and customer loyalty, and customer satisfaction has significant effect on customer loyalty. Keywords: customer value, CRM, customer satisfaction, customer loyalty